Pathophysiological Mechanisms of Sarcopenia in Aging and in Muscular Dystrophy: A Translational Approach - Paolo Bonaldo (Frontiers Research Topics, 2015)
Loss of muscle mass and increased fibrosis characterize both sarcopenia of aging and muscular dystrophy. Research is increasingly showing that these two conditions also share several pathophysiological mechanisms, including mitochondrial dysfunction, increased apoptosis, abnormal modulation of autophagy, decline in satellite cells, increased generation of reactive oxygen species, and abnormal regulation of signaling and stress response pathways. This Research Topic will cover several mechanisms involved in aging and dystrophic sarcopenia and explore the therapeutic potential of various strategies for intervention.